2019
DOI: 10.1158/1538-7445.sabcs18-pd1-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD1-11: nextMONARCH 1: Phase 2 study of abemaciclib plus tamoxifen or abemaciclib alone in HR+, HER2- advanced breast cancer

Abstract: Background Abemaciclib is a selective CDK4 & 6 inhibitor approved on a continuous dosing schedule for HR+, HER2- advanced breast cancer (ABC) as monotherapy (MONARCH 1) and in combination with endocrine therapy (ET). A previous Phase 1b (NCT01394016) cohort of HR+ ABC patients (pts) demonstrated efficacy of abemaciclib monotherapy (150mg and 200mg Q12H starting dose); given the small sample size and nonrandomized design the impact of the starting dose was unclear. nextMONARCH 1 (NCT02747004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interestingly, three different CDKIs 4/6 have recently been FDA approved for the treatment of lifelong aggressive and refractory HR+, Her2- BC therapy (palbociclib, PD0332991; ribociclib, LEE011; abemaciclib, LY835219) [ 149 , 150 , 151 ]. Several biomolecular pathways induced during the obese condition have been demonstrated to be in common with cancer mechanisms of tumor evasion, prompting the study of CDK inhibitors for the management of obesity disease [ 22 ].…”
Section: A Common Strategy In Cancer and Dio: Targeting Cell-cycle Pr...mentioning
confidence: 99%
“…Interestingly, three different CDKIs 4/6 have recently been FDA approved for the treatment of lifelong aggressive and refractory HR+, Her2- BC therapy (palbociclib, PD0332991; ribociclib, LEE011; abemaciclib, LY835219) [ 149 , 150 , 151 ]. Several biomolecular pathways induced during the obese condition have been demonstrated to be in common with cancer mechanisms of tumor evasion, prompting the study of CDK inhibitors for the management of obesity disease [ 22 ].…”
Section: A Common Strategy In Cancer and Dio: Targeting Cell-cycle Pr...mentioning
confidence: 99%
“…The study confirmed the single-agent activity of abemaciclib in heavily pretreated patients. The efficacy of abemaciclib monotherapy at 150mg was similar to 200 mg [ 25 ].…”
Section: Clinical Activity Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…The phase II nextMONARCH trial (NCT02747004) evaluated the safety and efficacy of abemaciclib plus tamoxifen or two different doses of abemaciclib monotherapy (150 or 200 mg) in women with previously treated HR + , HER2 − metastatic breast cancer (MBC) that progressed after prior chemotherapy and ET. In the abemaciclib monotherapy arms, mPFS was similar: 6.5 months in the abemaciclib 150 mg arm and 7.4 months in the abemaciclib 200 mg arm ( 18 ).…”
Section: Introductionmentioning
confidence: 96%